Assessing thyroid abnormalities in abnormal uterine bleeding: a comprehensive prospective study - N., Pooja; Choudary, Geeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Abnormal uterine bleeding (AUB) is a significant gynaecological concern affecting a substantial number of women, particularly during their reproductive years. It is often linked to various etiologies, including thyroid dysfunction, which can influence menstrual patterns through hormonal imbalances. The study explores the correlation between thyroid dysfunction (TDF) and AUB, aiming to establish whether thyroid hormone abnormalities are significant contributors to menstrual irregularities in women. By understanding this relationship, healthcare providers can better manage and treat AUB. Method: A prospective, observational study was conducted at Al-Ameen Medical College, Vijayapura, from November 2022 to May 2024, involving 100 women aged 15-60 years with AUB. Participants underwent detailed clinical examinations, ultrasonography, and baseline investigations, including thyroid function tests (T3, T4, and TSH). Exclusion criteria included pregnancy, bleeding disorders, and certain medical treatments. Data were analysed using SPSS software. Results: The study found that 55% of participants were euthyroid (EU), 38% were hypothyroid, and 7% were hyperthyroid. Significant correlations were observed between TDF and the type of bleeding, with hypothyroidism most common in prolonged and frequent cycles. The majority of cases were in women aged 31-35 years, highlighting a possible age-related vulnerability to TDF. Hormonal management was effective in most cases, particularly in those with underlying thyroid issues. Conclusion: Thyroid dysfunction, particularly hypothyroidism and euthyroidism, is significantly associated with AUB, especially in women aged 31-35 years. Regular thyroid function evaluation should be mandatory in AUB cases to ensure early detection and treatment, thereby improving reproductive health outcomes.